Estimates of Volume and Magma Input in Crustal Magmatic Systems from Zircon Geochronology: The Effect of Modeling Assumptions and System Variables - Caricchi, Luca; Simpson, Guy; Schaltegger, Urs (Frontiers in Earth Science, 2016)
Magma fluxes in the Earth’s crust play an important role in regulating the relationship between the frequency and magnitude of volcanic eruptions, the chemical evolution of magmatic systems and the distribution of geothermal energy and mineral resources on our planet. Therefore, quantifying magma productivity and the rate of magma transfer within the crust can provide valuable insights to characterise the long-term behaviour of volcanic systems and to unveil the link between the physical and chemical evolution of magmatic systems and their potential to generate resources. We performed thermal modelling to compute the temperature evolution of crustal magmatic intrusions with different final volumes assembled over a variety of timescales (i.e., at different magma fluxes). Using these results, we calculated synthetic populations of zircon ages assuming the number of zircons crystallising in a given time period is directly proportional to the volume of magma at temperature within the zircon crystallisation range. The statistical analysis of the calculated populations of zircon ages shows that the mode, median and standard deviation of the populations varies coherently as function of the rate of magma injection and final volume of the crustal intrusions. Therefore, the statistical properties of the population of zircon ages can add useful constraints to quantify the rate of magma injection and the final volume of magmatic intrusions. Here, we explore the effect of different ranges of zircon saturation temperature, intrusion geometry, and wall rock temperature on the calculated distributions of zircon ages. Additionally, we determine the effect of undersampling on the variability of mode, median and standards deviation of calculated populations of zircon ages to estimate the minimum number of zircon analyses necessary to obtain meaningful estimates of magma flux and final intrusion volume.